RNA-seq analysis of the influence of anaerobiosis and FNR on Shigella flexneri - Vergara-Irigaray, M; Fookes, M; Thomson, N; Tang, C; Vergara-Irigaray, M; Tang, C (BioMed Central, 2014)
Background: Shigella flexneri is an important human pathogen that has to adapt to the anaerobic environment in the gastrointestinal tract to cause dysentery. To define the influence of anaerobiosis on the virulence of Shigella, we performed deep RNA sequencing to identify transcriptomic differences that are induced by anaerobiosis and modulated by the anaerobic Fumarate and Nitrate Reduction regulator, FNR.Results: We found that 528 chromosomal genes were differentially expressed in response to anaerobic conditions; of these, 228 genes were also influenced by FNR. Genes that were up-regulated in anaerobic conditions are involved in carbon transport and metabolism (e.g. ptsG, manX, murQ, cysP, cra), DNA topology and regulation (e.g. ygiP, stpA, hns), host interactions (e.g. yciD, nmpC, slyB, gapA, shf, msbB) and survival within the gastrointestinal tract (e.g. shiA, ospI, adiY, cysP). Interestingly, there was a marked effect of available oxygen on genes involved in Type III secretion system (T3SS), which is required for host cell invasion and pathogenesis. These genes, located on the large Shigella virulence plasmid, were down regulated in anaerobiosis in an FNR-dependent manner. We also confirmed anaerobic induction of csrB and csrC small RNAs in an FNR-independent manner.Conclusions: Anaerobiosis promotes survival and adaption strategies of Shigella, while modulating virulence plasmid genes involved in T3SS-mediated host cell invasion. The influence of FNR on this process is more extensive than previously appreciated, although aside from the virulence plasmid, this transcriptional regulator does not govern expression of genes on other horizontally acquired sequences on the chromosome such as pathogenicity islands.